(untitled) (Journal of Engineering, 2006)
Stratified three-phase flow through horizontal pipe has been studied experimentally. The fluids used in the system are water, kerosene, and air. A closed loop flow system, which composed of 0.051 m inside diameter and 4 m length test pipe, is designed with facilities for measuring flow rate, pressure drop and thickness of each phase. The effects of gas, liquid flow rates and water liquid ratio (WLR) have been experimentally observed. It was found that liquid (water, and oil) thickness decreased when the gas flow rate is increased with constant liquid flow rate, and increased when the liquid flow rate is increased at constant gas flow rate. Pressure drop increased when the gas and/or liquid flow rate is increased. Three equations have been formulated, using the experimental data of the present work, to predict liquid, water thickness and system pressure drop in stratified three-phase flow in horizontal pipe. High correlation coefficients are obtained for these equations. The experimental results are compared with the results obtained from three-phase model of Taital, Barnea, & Brill (1995). The comparison showed that the predicted data which obtained from three-phase flow model Taital et al. (1995) is in good agreement with experimental data.